2011
DOI: 10.1103/physrevc.84.044302
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and high-spin band structure of the chiral-candidate nucleus134Pr

Abstract: Medium-and high-spin states of 134 Pr were populated using the 116 Cd( 23 Na, 5n) reaction and studied with the GAMMASPHERE spectrometer. Several new bands have been found in this nucleus, one of them being linked to the previously observed chiral-candidate twin-band structure. The ground state of 134 Pr could be determined through establishing a level structure that connects the two previously known long-lived isomeric states. Unambiguous spin-parity assignments for the excited states could be performed base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…It has been found that the negative-parity band structure of 132 La is rather similar to that of its isotone 134 Pr, recently reported in Ref. [15]. This similarity can be used to assist in the determination of the band configurations in 132 La, and also to draw further conclusions for the level scheme of this nucleus.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It has been found that the negative-parity band structure of 132 La is rather similar to that of its isotone 134 Pr, recently reported in Ref. [15]. This similarity can be used to assist in the determination of the band configurations in 132 La, and also to draw further conclusions for the level scheme of this nucleus.…”
Section: Discussionsupporting
confidence: 68%
“…In both nuclei, the ground-state spin-parity is 2 − , and a short I = 1 band (band 4 in 132 La and band 12 in 134 Pr [15]) is built on it. Also, in both nuclei a 6 − isomeric state exists close to the ground state with bands built on them.…”
Section: A Comparison With the Neighboring 134 Prmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most striking features was the observation of the nearly degenerate doublet bands built on the πh 11/2 ⊗ νh 11/2 configuration, interpreted as the manifestation of chiral symmetry breaking [1]. This phenomenon has been rather intensively investigated in recent years both experimentally [2][3][4][5][6][7][8] and theoretically [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…3 identified in the recent Gammasphere study of 134 Pr. 5 The interpretation of the doublet bands in this nucleus is a debated and still an open question. The chiral interpretation proposed originally in Ref.…”
Section: Axial Rotation Of a Triaxial Rotormentioning
confidence: 99%